2015
DOI: 10.5121/ijcsit.2015.7406
|View full text |Cite
|
Sign up to set email alerts
|

Review of Lane Detection and Tracking Algorithms in Advanced Driver Assistance System

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…True-negative (TN) means that the algorithm does not decide a lane mark while there is not a ground truth lane in reality. False-negative (FN) is the case where the algorithm does not detect any lane marking but ground truth data exist for this decision [22]. In this work, correct lane detection decision is given when the distance between detected lane marking and ground truth data points within a defined interval.…”
Section: Lane Detection Resultsmentioning
confidence: 99%
“…True-negative (TN) means that the algorithm does not decide a lane mark while there is not a ground truth lane in reality. False-negative (FN) is the case where the algorithm does not detect any lane marking but ground truth data exist for this decision [22]. In this work, correct lane detection decision is given when the distance between detected lane marking and ground truth data points within a defined interval.…”
Section: Lane Detection Resultsmentioning
confidence: 99%
“…Among the traditional lane line detection methods, some works of literature [13][14][15] have made a comprehensive summary of it summarized that the traditional lane line detection methods [16] are usually divided into three steps: image pre-processing, local feature extraction, and lane line fitting. Among them, local feature extraction is to capture local lane line information by using edge [17], texture [18], and color [19] features on the region of interest (ROI) [20] in the image, which is a key step of traditional lane line detection methods.…”
Section: Related Workmentioning
confidence: 99%
“…The lane markers along the roads must be properly detected and understood. However these lane markers tend to become unclear to the road users who are driving vehicles along the road when the weather changes [1,2] especially for advanced driver assistance systems [3][4][5] Road Safety Research (MIROS) in 2016 has shown that 156 drivers out of 44614 drivers had made illegal overtaking along roads with double solid road marking [6]. Foggy, snowy and rainy weather conditions cause difficulties on the road users to clearly detect the lane and correctly perceive the types of the lane markers and have turned out to be among the major factors that cause road crashes [7].…”
Section: Introductionmentioning
confidence: 99%